Maternal smoking during infancy increases the risk of allergic diseases in children: a nationwide longitudinal survey in Japan - Kenji Shigehara; Naomi Matsumoto; Mitsuru Tsuge; Kazuhiro Uda; Yukie Saito; Masato Yashiro; Takashi Yorifuji; Masanori Ikeda; Hirokazu Tsukahara (Allergy, Asthma & Clinical Immunology)
Abstract Background The incidence of allergic diseases has been increasing in Japan. In particular, a serious decline in the age of onset of allergic rhinitis has been observed. Passive smoking from parental smoking has a significant impact on children’s health; however, it is difficult to restrict smoking in the home. While various studies have previously reported on the relationship between passive smoking and the development of allergic diseases in children. However, there have been no reports on passive smoking and allergic diseases on a national scale. Methods Using Japanese national longitudinal survey data (n = 38,444) for newborns born between May 10 and 24, 2010, we assessed parental smoking habits when their children were 6 months old and investigated the association with the development of allergic diseases until the age of 5.5 years. The risk ratios and 95% confidence intervals for the development of different allergic diseases were analyzed after adjusting for potential confounders using Poisson regression with a robust error variance. Results The risk ratio for developing allergic rhinitis/allergic conjunctivitis (AR/AC) in children was significantly higher in the maternal smoking groups ( ≦ 10 cigarettes/day; RR 1.15, 95% CI 1.02–1.30; ≧11 cigarettes/day; RR 1.16, 95% CI 0.93–1.44). Furthermore, associations were found between the maternal smoking group in the presence of paternal smoking and the risk of developing bronchial asthma ( ≦ 10, RR 1.33 95% CI 1.17–1.52; ≧11, RR 1.71 95% CI 1.38–2.1), food allergy ( ≦ 10, RR 1.36 95% CI 1.12–1.63; ≧11, RR 1.25 95% CI 0.84–1.86), atopic dermatitis ( ≦ 10, RR 1.42 95% CI 1.22–1.66; ≧11, RR 1.6 95% CI 1.2–2.13), and AR/AC ( ≦ 10, RR 1.21 95% CI 1.07–1.36; ≧11, RR 1.35 95% CI 1.09–1.67). Conclusions Maternal smoking during infancy increases the risk of developing AR/AC in children. Considering paternal smoking, maternal smoking further increased the risk of developing allergic diseases in children, suggesting that reducing parental smoking at home may reduce the risk of developing allergic diseases in children.